The Why and How of Blended Finance : Recommendations to Strengthen the Rationale for and Efficient Use of Concessional Resources in Development Finance Institutions’ Operations - Mutambatsere, Emelly; Schellekens, Philip (International Finance Corporation, Washington, DC, 2021)
Blended concessional finance (BF), the use of catalytic capital from public or philanthropic sources to increase private sector investment—is becoming an important instrument to support the 2030 Agenda for Sustainable Development. Together with other Development Finance Institutions (DFIs), IFC has been at the forefront of developing and upholding high standards as an implementing entity of concessional resources. Building on these standards, this paper offers recommendations to further strengthen the rationale for and efficient use of blended concessional resources. Central among these is the need to unpack better the rationale for BF, which requires justifications for development impact, additionality and the use of concessionality. The paper discusses ways to deploy concessional finance more efficiently once the rationale is correctly identified and articulated. It argues that the Coronavirus (COVID-19) pandemic not only raises the urgency to deploy BF efficiently and effectively, it also represents an exceptional circumstance to consider the use of BF in portfolio.